THE EFFECT OF ADDITION OF MANGGIS (Garcinia mangostana) EXTRACT WITH DIFFERENT CONCENTRATION ON THE GROWTH AND LIABILITY OF VANAME SHRIMP (Litopanaeus vannamei) - angga wati; Hilyana, Sitti; Marzuki, Muhammad (Jurnal Perikanan Unram, 2020)
Effect of Addition of Mangosteen (Garcinia mangostana) Skin Extract with Different Concentration on Growth and Survival of Vaname Shrimp (Litopenaeus vannamei). The purpose of the study was to determine the effect of adding mangosteen peel extract with different concentrations on the growth and survival of vaname shrimp. This study used a Completely Randomized Design (CRD) consisting of 4 treatments and 3 replications to obtain 12 experimental units. In treatment 1 (control) without mangosteen peel extract, treatment 2 doses of mangosteen peel extract 6%, treatment 3 doses of mangosteen peel extract 8% and treatment 4 doses of mangosteen peel extract 10%. The parameters measured are absolute weight growth, survival and feed efficiency. The best treatment was obtained in treatment 4 with the addition of mangosteen peel extract (10%) with an absolute weight growth of 3.96 grams, 100% survival and 6.73 % of feed efficiency.